Drought shocks and labor reallocation in rural Africa: Evidence from Ethiopia - Arnold L. Musungu; Zaneta Kubik; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2023)
We study how rural households in Ethiopia adapt to droughts through labor reallocation. By using three waves of panel data and exploiting spatial-temporal variations in drought exposure, we find that households reduce on-farm work and increase off-farm self-employment in response to both short-term and persistent droughts, without abandoning family farming. Diversification into off-farm activities is driven by drought-related productivity declines in agriculture and contributes to consumption smoothing. Households with better access to markets and financial services find it easier to reallocate labor off-farm. Our results highlight the importance of strengthening the rural non-farm economy to enhance rural households' climate resilience.
Keywords: Q54; J21; J22; J43; O13; 330; Climate change; labor allocation; labor markets; Africa; Ethiopia